Estudo físico-químico e microbiológico de águas de poços tubulares da cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2006)
The water samples were collected in 30 well, distributed randomly in unconfined, confined and semi-confined aquifers from Manaus (Amazonas ? Brazil), during August/ 2004 and January/2005, and dry and rainny season. The variables physcal-chemical (pH, color, turbidity, electrical condutivity, ammonia, nitrite, chlorite, silica, sulfate, total hard, calcium hard, magnesium hard, Na, K, and Fe) and microbiological (coliform total, coliform fecal, and Heterotrophic bacteria) were determined. The statistical analysis of principal component (PCA) and cluster (HCA) were used to understand the date. The results revealed that physical-chemical and microbiological had the highest values during dry season, mainly coliform total, coliform fecal, electrical condutivity and nitrate. The most samples had values according to Brazilian Sanitary Law (ANVISA, law no 518 of 25/03/2004). However, depending on season and sampling site was observed contamination due to antrophogenic activity. The unconfined aquifer was major vulnerable to contamination by antrophogenic activity than confined and semi-confined. The PCA and HCA showed significantly difference bewteen dray and rainy season.
Keywords: Aquilíferos livres - Manaus (AM); Poços tubulares - Manaus (AM); Contaminação das águas subterrâneas; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS